NILAI-NILAI PENDIDIKAN KARAKTER DALAM FILM JUMBO KARYA RYAN ADRIANDHY DAN RELEVANSINYA TERHADAP PEMBELAJARAN - Rahma, Nafisa Aulia Nadia; Kumala, Sinta; Islami , Shava Aqiqoh Al; Nashrulloh, Muhammad Iqbal (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Character education currently faces significant challenges in shaping individuals who are not only cognitively intelligent but also morally strong amidst the flow of foreign culture. The purpose of this study is to discover the values ​​of character education in the local animated film Jumbo, directed by Ryan Adriandhy, and to analyze how these values ​​relate to learning in elementary schools. The meanings, symbols, and moral messages in the scenes and conversations of the characters in this study were analyzed through a qualitative approach using descriptive content analysis methods. Primary data were obtained through in-depth observation, while secondary data were obtained by reviewing literature related to the Independent Curriculum and pedagogy. The results show that the film Jumbo internalizes fourteen main educational character values. These values ​​include religiousness, honesty, tolerance, reading, social care, responsibility, discipline, hard work, independence, democracy, curiosity, patriotism, achievement, and communication. The results show that Don, the main character, demonstrates strong discipline and responsibility as a behavioral example for students. The relevance to learning is between the film's story and the structure of the Merdeka Curriculum, especially in terms of the dimensions of the Pancasila Student Profile such as "Noble Morals," "Mutual Cooperation," and "Independence." Furthermore, the film serves as an effective social-emotional learning tool to address bullying issues in elementary schools. Students are encouraged to cultivate empathy and moral courage to face bullying through the dynamics of relationships between characters. According to research, audiovisual media has the ability to transform abstract moral values ​​into concrete actions that are engaging and easily understood by children. These results are expected to help teachers use digital literacy to create a safe and character-building learning environment.